Cryptochrome-dependent magnetoreception in a heteropteran insect continues even after 24 h in darkness - Netušil, Radek; Tomanová, Kateřina; Chodáková, Lenka; Chvalová, Daniela; Doležel, David; Ritz, Thorsten; Vácha, Martin (Journal of experimental biology, 2021)
Sensitivity to magnetic fields is dependent on the intensity and color of light in several animal species. The light-dependent magnetoreception working model points to cryptochrome (Cry) as a protein cooperating with its co-factor flavin, which possibly becomes magnetically susceptible upon excitation by light. The type of Cry involved and what pair of magnetosensitive radicals are responsible is still elusive. Therefore, we developed a conditioning assay for the firebug Pyrrhocoris apterus, an insect species that possesses only the mammalian cryptochrome (Cry II). Here, using the engineered Cry II null mutant, we show that: (i) vertebrate-like Cry II is an essential component of the magnetoreception response, and (ii) magnetic conditioning continues even after 25 h in darkness. The light-dependent and dark-persisting magnetoreception based on Cry II may inspire new perspectives in magnetoreception and cryptochrome research.
Keywords: Cryptochromes; hmyz; Sensation; magnetické pole; čití, cítění; Darkness; Magnetic Fields; Animals; tma; Insecta; zvířata; kryptochromy